SMART and CVSS-Based System Vulnerability Prioritization Model - Sari Hartini; Rosi Kusuma Serli (LPPM Universitas Bina Sarana Informatika, 2026)
The increasing number of cybersecurity system vulnerabilities each year makes it difficult for organizations to determine the priority scale for remediation. Information system security is an essential aspect of maintaining the continuity of digital services against cyber threats. Poorly managed system vulnerabilities can increase the risk of exploitation by unauthorized parties. This study aims to develop a system vulnerability prioritization model using the SMART (Simple Multi-Attribute Rating Technique) and CVSS (Common Vulnerability Scoring System) methods. CVSS is used to measure the severity level of vulnerabilities based on technical characteristics such as the impact on the confidentiality, integrity, and availability of the system. Furthermore, the SMART method is applied to perform multi-criteria weighting processes in order to generate a more objective ranking of vulnerability handling priorities. The result of this model is a prioritized list of system vulnerabilities intended to assist system administrators in determining mitigation actions more effectively and efficiently. Through this approach, the vulnerability management decision-making process is expected to become more structured, measurable, and targeted.